Appraisement of Ranitidine Hydrochloride Tablet (USP150mg) Preparations from Few Selected Companies in Bangladesh - Islam, Mohd Aminul; Azad, Abul Kalam; Mohd Azizi, Wan (ANSI, 2013)
The study was aimed to evaluate the pharmaceutical properties of few selected generic products of ranitidine hydrochloride tablets available in retail pharmacies of Bangladesh. We collected 10 nationally manufactured generic ranitidine HCl tablets from local Market who followed USP specifications and examined their physical parameters and potency to check their compliance with the USP. The intention was to evaluate the quality of this pharmaceuticals after 20 years of implementing the National Drug Policy in 1982. All tested ranitidine tablet samples (Rt1-Rt10) were selectively collected from local retail pharmacies in Savar, Dhaka-1344, Bangladesh. Before purchasing the samples, their physical appearance, name of manufacturer, batch number, date of manufacturing, expiry date, manufacturing license number and Maximum Retail Price (MRP) were properly checked. The various parameters of the selected samples such as diameter, shape, size, weight variation, thickness, hardness, disintegration, dissolution and potency have been determined according to the American Pharmacopoeia USP 27 requirements. It was found that all ten selected products met the USP 27 specifications. The differences in hardness among the tablets were significant. Interestingly, dissolution profiles of some tablet products were not weighty different from one another, whereas those of tablets were significantly different. However, all brands complied with USP 27. It could be concluded that the selected ranitidine HCl tablets met the required USP specifications and are considered quality products in terms of the mentioned parameters.